Transforming Islamic Boarding School Education: Institutional Modernization and Quality Improvement in Tebuireng Jombang - Lukman Hakim; Suwandi Suwandi; Muhammad Hasyim; Erika Mei Budiarti; Aji Wahyudin (STAI Hubbulwathan Duri, 2025)
This study examines the educational transformation and institutional modernization of Tebuireng Islamic Boarding School in Jombang, Indonesia. The focus is on enhancing educational quality and reforming governance to meet the evolving demands of society and educational standards. A qualitative case study approach was employed, utilizing in-depth interviews, participatory observation, and analysis of institutional documents to gather comprehensive data on internal processes and structural changes. Findings reveal that transformation at Tebuireng is largely driven by the leadership’s growing awareness of the importance of educational quality and community expectations for graduates who are both religiously grounded and academically proficient. A key factor in this shift is the transition from a charismatic leadership style to a collective-delegative model. This change has fostered a more professional and innovative governance system and enhanced the recruitment and training of competent human resources. As a result, the school has witnessed improved graduate quality, rising public interest, and a stronger reputation as an adaptive, quality-focused pesantren. The study underscores the significance of participatory leadership and institutional responsiveness in pesantren modernization. The governance shift has enabled Tebuireng to maintain traditional Islamic values while adopting professional educational practices. This research contributes to the theoretical understanding of institutional transformation and participatory leadership in Islamic education. Practically, it offers a replicable model for other pesantren seeking modernization without compromising core religious principles.